2018
DOI: 10.1021/acs.iecr.8b00311
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Agglomeration Behaviors in High Temperature Gas–Solid Fluidized Beds with Liquid Injection

Abstract: An induction heating fluidized bed with liquid injection was designed to mimic the exothermic process of particles in industrial olefin polymerization fluidized beds. The effects of liquid injection flow rate on agglomeration behaviors were investigated through the characterization of agglomerate size and mass. Agglomeration mechanisms were proposed based on the experimental data of bed pressure drop, axial temperature distribution, and microscale visualization. Results have revealed that, with the increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…In rainy or snowy weather or when the temperature is low at night, the formation of a liquid bridge can cause dust particles to deposit on photovoltaic panels (Dormann and Schmid 2015). In addition, gravity and van der Waals forces may cause the deposition of dust particles on photovoltaic panels (Shi et al 2018). Our previous studies emphasised the dust particles deposited on photovoltaic panels as a result of the charged mechanism induced by a significant particle collision effect.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In rainy or snowy weather or when the temperature is low at night, the formation of a liquid bridge can cause dust particles to deposit on photovoltaic panels (Dormann and Schmid 2015). In addition, gravity and van der Waals forces may cause the deposition of dust particles on photovoltaic panels (Shi et al 2018). Our previous studies emphasised the dust particles deposited on photovoltaic panels as a result of the charged mechanism induced by a significant particle collision effect.…”
Section: Introductionmentioning
confidence: 97%
“…Previous research (Hanai et al 2011;Elminir et al 2006;Liu et al 2021aLiu et al ,2019aLiu et al ,2021bLu and Zhang 2018;Lu Lu-Yi et al 2008;Dormann and Schmid 2015;Shi et al 2018) has mainly analysed and discussed the factors influencing dust deposition characteristics. However, the dust deposition process is a complex phenomenon that is influenced by the coupled effects of gravity, buoyancy, van der Waals, drag, contact, electrostatic, and liquid bridge forces.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the fluidization patterns of Geldart group B particles may transfer toward group A and finally to group C with continuous injection of liquid. Specifically, group B particles were observed to expand homogeneously with liquid injection, exhibiting a typical feature of group A particles . As the liquid amount continues to increase, particle agglomeration takes place .…”
Section: Introductionmentioning
confidence: 97%
“…6 Similar results have been extensively reported. 7,8 The abovementioned trend is caused by the combined effect of the liquid bridge force and gas−solid drag force. 9 In view of the whole bed, the drag force tends to fluidize the particles, whereas the liquid bridge force is prone to bond the particles together, maintaining the bed in a stable manner.…”
Section: Introductionmentioning
confidence: 99%
“…However, the acquisition of aggregation kernel and breakage kernel is difficult because they are different under different conditions. 25 Thus, it is hard to investigate the process of liquid-induced agglomeration through the discrete element method or the population balance method when simulating a large-scale reactor or lacking appropriate kernel functions. In addition, no quantitative characterization of agglomeration rates, mass fraction of agglomerates, and particle size distribution has been carried out; meanwhile, most of them lack experimental validation.…”
Section: Introductionmentioning
confidence: 99%